Picture Surface Illusion: Small Effects on a Major Axis. (January 2014) - Mastandrea, Stefano; Kennedy, John M; Wnuczko, Marta
Perception of 2-D ellipses on a picture surface is inaccurate—if the ellipses depict circles that are tilted in 3-D, receding from the viewer (Hammad, Kennedy, Juricevic, & Rajani, 2008a, Perception, 37, 504–510). Notably, the minor axis of the ellipse is seen as larger than is true. This illusory effect could be due to the simultaneous presence of optical information for the 2-D ellipse and optical information for the 3-D tilted circle. The optical information for the circle may bias vision's use of the optical information for the ellipse. This theory predicts that illusory effects should occur on the major axis as well as the minor axis; but, we argue, the major axis effect should be smaller than the minor axis effect. We confirm the prediction. Observers looked at target ellipses depicting tops of tilted cylinders. In one experiment observers chose a match for the target from choice sets of seven 2-D ellipses. In the second, observers used the method of adjustment. Both axes were overestimated, the minor axis more than the major, as the theory suggested. We point out that the relative size of the effects matters to the theory, and so the small effect counts for a lot.